2016
DOI: 10.1111/coa.12703
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of isopeptide bonds and corneodesmosin in middle ear cholesteatoma

Abstract: These results indicate that the production of CDSN is likely to be suppressed in cholesteatoma, which would account, at least in part, for the mechanical fragility and increased permeability of the cholesteatoma epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In the last decade it has become obvious that there is not one gene suitable for use of normalisation for all tissue types [40]. In the field of middle ear research many different genes have been used, such as B2M [52], PPIA [9], ACTB [33,34], HPRT1 [35] and GAPDH [36][37][38][39]. Interestingly, all articles published to this date use only one gene for normalisation, even though it has been abundantly shown that this is not sufficient for reliable analysis [40].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade it has become obvious that there is not one gene suitable for use of normalisation for all tissue types [40]. In the field of middle ear research many different genes have been used, such as B2M [52], PPIA [9], ACTB [33,34], HPRT1 [35] and GAPDH [36][37][38][39]. Interestingly, all articles published to this date use only one gene for normalisation, even though it has been abundantly shown that this is not sufficient for reliable analysis [40].…”
Section: Plos Onementioning
confidence: 99%
“…QPCR has been used in several studies related to diseases of the middle ear. However, there seems to be little consensus as to which reference genes to use for normalisation, leading to the use of several different genes without proper establishment of which genes are appropriate [9,[31][32][33][34][35][36][37][38][39]. To be able to obtain reliable results the use of stably expressed reference genes for normalisation is essential [40].…”
Section: Introductionmentioning
confidence: 99%